CORRELATION OF CERVIC MUCOUS VISCOSITY WITH ESTROGEN CONCENTRATION DURING ESTRUS IN ACEH CATTLE - Thasmi, Cut Nila; Listin, Cantika Tamara; Husnurrizal, Husnurrizal; Sutriana, Amalia; Herrialfian, Herrialfian; Hafizuddin, Hafizuddin; Adam, Mulyadi; Dasrul, Dasrul; Siregar, Tongku Nizwan (Buletin Veteriner Udayana, 2023)
The viscosity of cervical mucus is affected by the concentration of estrogen. This study aims to determine the relationship between the viscosity of cervical mucus with the concentration of estrogen in Aceh cattle in the success of mating. This study used four female Aceh cattle, aged 3-7 years and weighing 150-250 kg, had given birth, and had two regular estrus cycles. All aceh cattle were synchronized with PGF2? (dinoprost tromethamine inj., Lutalyse®, Zoetis US) by the two shoot method intramuscularly. Cervical mucus collection was performed by aspiration on the day of estrus. The cervical mucus viscosity measurement is done by looking at the spinnbarkeit value. Estrogen concentration was measured by enzyme linked immunosorbant assay (ELISA). The data obtained in this study were analyzed using the Pearson correlation test. The results showed that the average viscosity of cervical mucus in Aceh was 11.8±4.6 cm, and the average concentration of estrogen in Aceh cattle during estrus was 106.5±15.8 pg/ml. The correlation between cervical mucus viscosity and estrogen concentration was 0.983. The conclusion of this study is that the higher the concentration of estrogen, the viscosity of cervical mucus will decrease so that the spinnbarkeit value will increase. It is necessary to conduct further studies related to the electrochemical characteristics of cervical and vaginal mucus during estrus including the value of ferning typology, electrical resistance vaginal mucus (ERVM), pH, sodium, magnesium, calcium and other cations that affect estrus performance in Aceh cattle.